The Influence of Work-Life Balance on Teacher Performance in Integrated Islamic Primary School - Karina Karina; Johar Permana; Nugraha Suharto (International Journal of Pedagogy and Teacher Education, 2025)
This study aims to analyze the influence of work-life balance on the performance of integrated islamic primary school teachers. Teacher performance is measured based on five indicators: work quality, timeliness, initiative, ability, and communication. Work-life balance in this study encompasses three indicators: time balance, involvement balance, and satisfaction balance. The research employs a quantitative method with a correlational approach. The total sampling technique was applied due to the relatively small population of 16 teachers, enabling comprehensive data collection. This sampling technique ensures that all population characteristics are fully represented without the need for random sample selection. Consequently, this method reduces the potential for bias in respondent selection and enhances research result accuracy. Data was collected through structured questionnaires and analyzed using SPSS 29. The research findings reveal that work-life balance contributes to teacher performance with a determination coefficient of 35%. This means that 35% of teacher performance variability can be explained by work-life balance, while other factors likely influence the remaining 65%. The study emphasizes the importance of work-life balance in improving teacher performance. Therefore, schools are recommended to develop policies that support work-life balance, including better workload management, schedule flexibility, and teacher welfare programs. Further studies with a larger sample size are necessary to obtain more representative and comprehensive results.